2021
DOI: 10.1021/acsomega.1c01551
|View full text |Cite
|
Sign up to set email alerts
|

Nanobubble-Assisted Flotation of Apatite Tailings: Insights on Beneficiation Options

Abstract: Processing of materials that originated from tailings of industrial plants (with a wide range of particle size distribution, “PSD”) without grinding has several advantages since mines are faced with a lot of pressure to minimize their environmental impacts. This article indicates that the introduction of submicron bubbles (known as nanobubbles, “NBs”) to conventional flotation could improve the separation efficiency of valuable minerals from their associated gangue phases. It was demonstrated that metallurgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…The highest S.E can be observed when starch and PGA were 50 and 300 g/t, respectively. The observed improvements in flotation separation corroborate findings reported elsewhere on the beneficial effects of a narrow particle size distribution 27 , 28 and surface roughness 39 , 40 . Besides the superior properties observed from using PGA, surface analyses were considered to assess PGA interaction with mineral surfaces.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The highest S.E can be observed when starch and PGA were 50 and 300 g/t, respectively. The observed improvements in flotation separation corroborate findings reported elsewhere on the beneficial effects of a narrow particle size distribution 27 , 28 and surface roughness 39 , 40 . Besides the superior properties observed from using PGA, surface analyses were considered to assess PGA interaction with mineral surfaces.…”
Section: Resultssupporting
confidence: 89%
“…Understanding and controlling any GA-separation reagent interactions is critical to ensure that the required downstream process efficiency and integrity of the whole value chain are maintained. Such an understanding would be essential, particularly for flotation separation, where the separation could be efficient in the specific particle size range (mainly −100 + 25 µm) 27 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] The addition of reagents during NB generation has been reported to improve flotation performance . [3,[18][19][20] Nazari et al, [19] during coarse flotation of pure quartz found MIBC to be more effective compared to pine oil and dodecyl amine (DDA) when added during the nanobubble generation. This is due to the decrease in surface tension of the liquid, which translates into production of finer bubbles .…”
Section: Discussionmentioning
confidence: 99%
“…A higher selectivity index S extrapolates better selectivity for the process . [17,18] The flotation rate constant k, for each scenario, was calculated using the firstorder equation 2. [5] Pure quartz (Single) -−100 + 48 µm 23% mass recovery [6] Pure quartz (Single) MIBC −425 + 106 µm +5-20% mass recovery [7] Pure quartz (Single) A65 −425 + 106 µm + 15-20% mass recovery [7] Apatitic ore -−75 µm +8.9% recovery, −1.9% grade [6] Phosphate ore Flo-Y-S −38 µm +35.4% recovery, +3.4% grade [8] Hematite ore TD-II −150 µm +16.0% recovery, -grade [9]…”
Section: Flotationmentioning
confidence: 99%
“…The other part relates to the cell drawbacks including the inability to produce small bubbles, short retention time for such fine particles, and poor and inefficient turbulence. To overcome these obstacles, researchers either enlarged particle size using flocculation-flotation processes (Yin et al, 2011;Li et al, 2021), applied micro/nano-bubble assisted flotation (Fan et al, 2012;Chipakwe et al, 2021), or utilized intensified cell turbulence (Schubert, 2008;Safari et al, 2014;Testa et al, 2017;Hoseinian et al, 2019). Researchers changed the cell hydrodynamics and invented reactor-separator flotation cells creating remarkable gas hold-up, small bubble sizes, and intensive turbulences (Imhof 2006;Jameson, 2010;Cole et al, 2020).…”
Section: Introductionmentioning
confidence: 99%